Magnaporthe oryzae effector AvrPik-D targets a transcription factor WG7 to suppress rice immunity - Tao Yang; Linlin Song; Jinxian Hu; Luao Qiao; Qing Yu; Zonghua Wang; Xiaofeng Chen; Guo-dong Lu (Rice, 2024)
Abstract Rice blast, caused by the fungal pathogen Magnaporthe oryzae, is one of the most devastating diseases for rice crops, significantly affecting crop yield and quality. During the infection process, M. oryzae secretes effector proteins that help in hijacking the host's immune responses to establish infection. However, little is known about the interaction between the effector protein AvrPik-D and the host protein Pikh, and how AvrPik-D increases disease severity to promote infection. In this study, we show that the M. oryzae effector AvrPik-D interacts with the zinc finger-type transcription factor WG7 in the nucleus and promotes its transcriptional activity. Genetic removal (knockout) of the gene WG7 in transgenic rice enhances resistance to M. oryzae and also results in an increased burst of reactive oxygen species after treatments with chitin. In addition, the hormone level of SA and JA, is increased and decreased respectively in WG7 KO plants, indicating that WG7 may negatively mediate resistance through salicylic acid pathway. Conversely, WG7 overexpression lines reduce resistance to M. oryzae. However, WG7 is not required for the Pikh-mediated resistance against rice blast. In conclusion, our results revealed that the M. oryzae effector AvrPik-D targets and promotes transcriptional activity of WG7 to suppress rice innate immunity to facilitate infection.